Analysis of SSR and AFLP Markers to Detect Genetic Diversity Among Selected Clones of Grapevine (Vitis vinifera L.) cv. Keshmeshi - Doulati Baneh, H.; Mohammadi, S.A.; Mahmoudzadeh, H.; de Mattia, F.; Labra, M. (South African Journal of Enology and Viticulture, 2016)
To assess the genetic differences between clones of grapevine (Vitis vinifera L.) cv. Keshmeshi, ten selected clones from a clonal selection programme were analysed by 23 Simple Sequence Repeats (SSR) and seven AFLP primer combinations. No intra-varietal differences between the clones could be detected by SSRs, whereas eight out of the 499 AFLP fragments generated by the seven primer combinations were polymorphic. The number of markers ranged from 44 (E34-M34) to 97 (E31-M32), with an average of 71.3 fragments per primer combination. Cluster analysis based on the AFLP data separated all the clones of Keshmeshi in two groups. The first group included nine white berry skin clones without any genetic differences, and the second group with only a red berry skin clone. AFLP could only distinguish the red berry clone of Keshmeshi from other white berry clones.